2014
DOI: 10.1177/0004867414563187
|View full text |Cite
|
Sign up to set email alerts
|

Mental illness and housing outcomes among a sample of homeless men in an Australian urban centre

Abstract: This study provides evidence to support an innovative support model for homeless people in Australia and contributes to the limited Australian research on mental illness in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 45 publications
2
23
2
Order By: Relevance
“…In a sample of 1158 people experiencing homelessness in Western Australia, half had trimorbidity (the coexistence of substance use, serious medical problem and mental illness) 16 . In an intervention study of homeless men in Sydney, 71% of respondents at baseline reported a previous psychiatric diagnosis, and 20% fulfilled criteria for post‐traumatic stress disorder in the past month 17 …”
Section: Health As Consequence and Cause Of Homelessnessmentioning
confidence: 99%
See 1 more Smart Citation
“…In a sample of 1158 people experiencing homelessness in Western Australia, half had trimorbidity (the coexistence of substance use, serious medical problem and mental illness) 16 . In an intervention study of homeless men in Sydney, 71% of respondents at baseline reported a previous psychiatric diagnosis, and 20% fulfilled criteria for post‐traumatic stress disorder in the past month 17 …”
Section: Health As Consequence and Cause Of Homelessnessmentioning
confidence: 99%
“…16 In an intervention study of homeless men in Sydney, 71% of respondents at baseline reported a previous psychiatric diagnosis, and 20% fulfilled criteria for post-traumatic stress disorder in the past month. 17…”
Section: Health As Consequence and Cause Of Homelessnessmentioning
confidence: 99%
“…It is important to note that comorbidities are common in homeless populations (The Lancet 2014). In particular, a significant proportion of homeless individuals suffer from substance dependence and mental illness (The Lancet 2014; Fazel, Geddes et al 2014;Cheung, Somers et al 2015;Spicer, Smith et al 2015). Homelessness, substance abuse and mental illness have all individually been associated with higher use of emergency departments and higher rates of hospitalisation (Kushel, Vittinghoff et al 2001;Kushel, Perry et al 2002;Culhane, Metraux et al 2002;Kim, Kertesz et al 2006;Chartier, Carrico et al 2012), and so the impact on health service use and costs are compounded when these circumstances are clustered together.…”
Section: Relationship Between Homelessness and Healthmentioning
confidence: 99%
“…Recent systematic reviews have highlighted the lack of consensus in definitions of housing stability [ 5 , 6 ]. Most studies categorize participants as either housed or homeless [ 7 , 8 , 9 ] and include relatively few dimensions in defining housing trajectories, such as type of accommodation (e.g., living with family or friends, in supportive housing, etc.) and housing duration (e.g., 90 consecutive days, or longer) [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%